Tinjauan Ketepatan Kode Diagnosa dan External Cause Kecelakaan Lalu Lintas di IGD RSIJ Pondok Kopi - Aneu Rosliana; Laela Indawati; Puteri Fannya; Noor Yulia (Yayasan Literasi Sains Indonesia, 2023)
Codification is the activity of classifying diseases based on certain criteria. Coding of disease diagnoses according to ICD-10 rules. One form of classification coding is using External Cause, which is a code used to classify the external cause of a disease caused by accidents, injuries, poisoning, burns, or side effects of drugs. This study was conducted at the Emergency Department of the Jakarta Islamic Hospital Pondok Kopi with the aim of the study to determine the percentage of accuracy of diagnosis and external cause codes and identify SPO related to classification coding. This study uses a quantitative descriptive method, with the technique of taking total sampling or saturated samples on 66 medical records for the period July 2022. The results of the research obtained with 66 samples related to traffic accident patients. Obtained the results of the accuracy of 66 appropriate injury diagnosis codes (100%) and 0 inappropriate (0%). The results of the accuracy of the external cause code obtained 66 (0%) external cause codes cannot be assessed because external cause coding activities have not been carried out. Only have SPO specifically for coding diagnoses in general, SPO specifically for external causes is not yet available. Of the 5 inhibiting factors studied, 3 inhibiting factors were obtained that caused the inaccuracy of external cause coding, namely Man, Money, and Material.